Synthesis and Crystal Structures of Transition Metal(II) Fluoridometallate(IV) Hydrates of Neptunium and Plutonium: AIIMIVF6·3H2O (AII = Mn, Zn; MIV = Np, Pu). Issue 23 (28th May 2020) - Scheibe, Benjamin; März, Juliane; Schmidt, Moritz; Stumpf, Thorsten; Kraus, Florian
Abstract : Transition metal(II) fluoridometallates(IV) A II M IV F6 · 3H2 O ( A II = Mn, Zn; M IV = Np, Pu) were synthesized from NpO2 or PuO2 and the respective transition metal chlorides from hydrofluoric acid under mild conditions. The olive‐green (Np) or orange (Pu) compounds were obtained as single‐crystals and the respective structures were determined by single‐crystal X‐ray diffraction. In the isotypic compounds, chains of edgesharing tricapped trigonal prismatic polyhedra ∞ 2 [ M IV F8/2 (H2 O)1/1 ], are present and an overall three‐dimensional network structure is observed in which the A II and M IV atoms are arranged according to the simple NaCl structure type. Within the respective U–Pu series of the Zn and Mn salts the cell volumes and the M IV –F distances decrease due to the actinoid contraction. Abstract : Transition metal(II) fluoridometallate(IV) hydrates of Np and Pu were synthesized from NpO2 /PuO2 and the corresponding transition metal chlorides in hydrofluoric acid suspensions. The compounds are isotypic to the U compounds, in which the actinoid atom is nine‐coordinate. Within the U–Pu series the M IV –F distances and the cell volumes decrease due to the actinoid contraction.